2021
DOI: 10.1038/s41598-021-82282-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity and antidiabetic effects of the dairy bacterium Propionibacterium freudenreichii MJ2 in high-fat diet-induced obese mice by modulating lipid metabolism

Abstract: Obesity can cause chronic metabolic disorders such as type 2 diabetes, hyperlipidemia, and nonalcoholic fatty liver diseases. The aim of this study was to investigate the antiobesity and antidiabetic effects of the dairy bacterium P. freudenreichii MJ2 isolated from raw milk using 3T3-L1 cells and high-fat diet (HFD)-induced obese mice. Lipid accumulation and the expression levels of genes related to lipid metabolism, such as preadipocytic gene (Pref-1), adipogenic genes (PPARγ and C/EBPα), and lipogenic genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Adipogenesis is a process that preadipocytes differentiate into mature adipocytes through the regulation of multiple transcription factors and lipogenic genes. C/EBPα is one of the CEBP members and expressed at the early stage of adipogenesis [60].At the late stage of differentiation, downstream key enzymes controlling fatty acids synthesis including FAS and ACC are expressed to promote adipogenesis and lipid accumulation in adipocytes [61,62]. Pref-1 is an early negative regulator of adipogenic differentiation [63].…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis is a process that preadipocytes differentiate into mature adipocytes through the regulation of multiple transcription factors and lipogenic genes. C/EBPα is one of the CEBP members and expressed at the early stage of adipogenesis [60].At the late stage of differentiation, downstream key enzymes controlling fatty acids synthesis including FAS and ACC are expressed to promote adipogenesis and lipid accumulation in adipocytes [61,62]. Pref-1 is an early negative regulator of adipogenic differentiation [63].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the organ body ratio indicates organ congestion, edema, hyperplasia, and hypertrophy, whereas a decrease indicates organ atrophy and other degenerative changes. NAFLD was a metabolic disease caused by excessive accumulation of fat in the abdomen and liver, which may result from HFD ( An et al., 2021 ). The results of our present study indicated that relative weight of liver and adipose in the treatment groups were smaller than those of the Model Group ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…BAA6 culture supernatant (BAA6-CM) was obtained as with the previous method [32]. Dead BAA6 was prepared as previously reported [33]. Briefly, BAA6 cells, grown to 10 9 colony-forming units (CFU)/mL, were centrifugated at 3000× g at 4 • C for 15 min.…”
Section: Preparation Of Bacterial Cultures Baa6-cm and Dead Baa6mentioning
confidence: 99%